Analisis Kualitas Sumber Daya Manusia, Dan Sistem Pengendalian Intern Pemerintah (SPIP) Terhadap Efektivitas Penggunaan Sistem Keuangan Desa (SISKEUDES) - Sindrila Dwita Eprilsa; Gideon Setyo Budiwitjaksono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine how the influence of the quality of human resources, and the government's internal control system on the effectiveness of the use of the village financial system (Siskeudes) in Kedungpring District, Lamongan, East Java. The research method is carried out using quantitative methods. Data analysis of the use of SPSS 25 assistance. The results showed that there was a significant influence between the quality of human resources on the effectiveness of the use of SISKEUDES, and the internal control system which had a significant effect on the effectiveness of the use of SISKEUDES. And obtained the R Squere value of 0.579 or 57.9%. Keywords: Quality of Human Resources, Government Internal Control System, Effectiveness of Use of Siskeudes.